Peran Guru Sosiologi Dalam Meningkatan Nilai Toleransi Pada Siswa Di SMA Negeri 1 Cikeusal Kabupaten Serang Banten - Kamelia, Kamelia; Soetrisnaadisendjaja, Denny; Widiansyah, Subhan (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
Teachers have an important role in educating students at school, especially in efforts to improve the quality of human resources, this is related to intolerant attitudes and behavior that every student must have. An attitude of tolerance needs to be instilled in order to create unity and peace so that students are able to accept differences, respect opinions, respect existing diversity. During sociology learning activities at school, many students find an intolerant attitude, such as not respecting the opinions of friends who provide their views on a problem, not paying attention to the teacher who is delivering the learning material, leaving the class while the lesson is still in progress and often interrupting friends' conversations. The aim of this research is to determine the value of implementing tolerance in students and to determine the impact of the results of the implementation carried out by sociology teachers through learning materials in the classroom. This research uses qualitative research methods with descriptive methods. The sources for this research are primary data and secondary data, with informants from school principals, sociology teachers and students. data was collected through observation, interviews and documentation. The research results show that the attitude of tolerance that is instilled is related to the value of helping each other, respecting other people's opinions, being able to accept existing differences of opinion and being able to work together. The teacher's efforts to increase the value of tolerance in students are by using sociology material as a learning tool related to the value of tolerance in social life.